Shade and Thermal Comfort in Courtyards: Experimental versus Simulation Results - Victoria Patricia López-Cabeza; Eduardo Diz-Mellado; Carlos Alberto Rivera-Gómez; Carmen Galán-Marín (Buildings, 2022)
Outdoor comfort is gaining attention in the design of our cities to face the current context of rising temperatures. Although simulation is required to inform the early design stage of projects considering outdoor space and strategies to improve their thermal performance, different tool options must be compared through monitoring to determine the accuracy of their modeling. This study analyses the thermal comfort benefits of the installation of a shading device in a courtyard in the Mediterranean climate. In the study, two simulation workflows were analyzed, one using ENVI-met software and the other using the Ladybug Tools, to evaluate their performance. Air temperature monitoring data were used to validate and calibrate the simulations. Then, both were used to compute the Universal Thermal Climate Index (UTCI) to evaluate comfort. The results show that the simulation reproduced an air temperature reduction when the shading was installed, but this was not as high as the monitoring results (up to 13.7 °C). In the UTCI, in contrast, the two simulation workflows provided contradictory results. These differences were explained by analyzing the different parameters affecting comfort and the mean radiant temperature, and the air temperature was found to be the parameter most affecting the UTCI in this context. Thus, future research should focus on improving the accuracy of the simulations of these two parameters.